They and Alone. The Vulnerability and Absence in Galician Exile’s Literary Production - Garrido González, Ana (Madrygal. Revista de Estudios Gallegos, 2017)
In this paper, making use of some examples, we will look into the reasons that explain why in some texts, written by authors in exile after the 1936’s coup d’état, the concept of the 'widow of a living husband', as a constituent model of the waiting, stops being just a metaphor of the femininity as an embodiment of the nation. The creation of memory and symbolic-cultural identity of the Galician exile and emigration is done with a collective epic tone. Therefore, the transnational community must be linked with the idea of the return. Hence the central importance of the absence and waiting representation in the works done in the exile and the presence of the widow of a living husband as a representation of the nation. Consequently, in many occasions, the exiled authors address these women as historical subjects deserving memory and connected with the present. As happened in the section “Viúvas de vivos” from Follas Novas, focusing in their onerous situation gives them back the voice taken by the mythification and disembodiment. This is possible because these authors write from an exilic position in the literary system, in like manner as Rosalía de Castro wrote for the only reason of being a woman. From this marginal position, they were forced to confront the nineteenth-century, patriarchal values which were the basis of the naturalized bond between nation and culture loses strength, bringing closer other interpretations once left out by the essentialist nationalism and now needed to rebuild the national identity from new ideological positions coming from the experience of the civil war and from the necessity of coexistence and dialogue with other cultures.
Keywords: Widow of a Living Husband; Nation; Luís Seoane; Rafael Dieste; Exile.